The Effect of Administration of The Utilization Of Toga as a Stunting Prevention Drug on The Knowledge Level of The Community of Sekotong Central Village. - Rachmawati, Indah; Kiromah, Naelaz Zukhruf Wakhidatul; Asti, Arnika Dwi (Prosiding University Research Colloquium, 2022)
Stunting is a condition of failure to thrive in children under five years old (toddlers) due to chronic malnutrition and repeated infections, especially in the first 1,000 days of life (1000 HPK). The NTB Health Office (Dikes) noted that in 2018, the average stunting rate in NTB was 33.49%. West Lombok is ranked number three after East Lombok and Dompu, namely West Lombok 33.61%, East Lombok 43.52%, and Dompu 33.83%. The causes of stunting can be divided into direct and indirect causes. The direct causes of stunting include lack of nutritional intake in children and the presence of recurrent disease. The indirect causes of stunting are the lack of stimulation (stimulation) and poor personal and environmental hygiene. Malnutrition and stunting are two interrelated problems. Stunting prevention can be done by using family medicinal plants as traditional medicines in the form of herbs. The community service program was carried out with the aim of increasing the knowledge of the Sekotong Tengah village community regarding the use of TOGA as herbal medicine to prevent stunting. This activity is carried out by means of education and training on the use of TOGA plants as herbs to prevent stunting. Education is carried out by the method of counseling and filling out questionnaires. This method is used to analyze the effect of counseling on the level of community knowledge. This type of analysis is pre-experimental with one group pre-post test design. Community service was carried out in the village of Sekotong Tengah, West Lombok Regency. The target in this community service is the village community of Central Sekotong, West Lombok Regency. Data collection techniques in the form of direct interviews with respondents and measuring the level of knowledge through the provision of questionnaires before and after counseling. The statistical test used is the paired t-test. From the results of the analysis that has been carried out, there is a change in the level of community knowledge. Prior to the counseling, it was known that 50% of respondents had less knowledge, 30% of respondents had sufficient knowledge, and 20% of respondents had less knowledge. After counseling, 20% of respondents have sufficient knowledge, and 80% of respondents have good knowledge. The results of the pretest and posttest scores before and after the counseling showed significant differences, indicating an increase in public knowledge that occurred after the counseling.